2018
DOI: 10.1111/jep.12923
|View full text |Cite
|
Sign up to set email alerts
|

Perception, attitude, and satisfaction of paediatric physicians and nurses towards clinical practice guidelines at a university teaching hospital

Abstract: The paediatric doctors, and nurses have a great perception and satisfaction and positive attitude towards CPGs in general, towards the paediatric diabetic ketoacidosis CPG in particular, which in turn had a positive impact on the acceptability and implementation of the CPGs. These findings could help in sustaining a safe and high-quality health care environment through implementation of evidence-based CPGs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…Physicians indicated that their documentation system has several loopholes and that they tend to forego documentation of administrative issues, which contributes to poor records yet, paradoxically, they said that documentation is crucial for drug prescription purposes. This argument correlates with systematic review findings of Hasanain et al, (2014), that although the KSA government introduced the Electronic Medical Record [19] in 1988, the documentation system faced the challenges of software complexity, cost overruns, privacy concerns, inadequate uniform standards, and inadequate vendor maintenance and support [36]. Insomnia medications such as BZDs or Z-drugs are two prescriptive classes of drugs that require adequate documentation to ensure that patients are well monitored.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Physicians indicated that their documentation system has several loopholes and that they tend to forego documentation of administrative issues, which contributes to poor records yet, paradoxically, they said that documentation is crucial for drug prescription purposes. This argument correlates with systematic review findings of Hasanain et al, (2014), that although the KSA government introduced the Electronic Medical Record [19] in 1988, the documentation system faced the challenges of software complexity, cost overruns, privacy concerns, inadequate uniform standards, and inadequate vendor maintenance and support [36]. Insomnia medications such as BZDs or Z-drugs are two prescriptive classes of drugs that require adequate documentation to ensure that patients are well monitored.…”
Section: Discussionmentioning
confidence: 60%
“…In Saudi Arabia, the few quantitative studies [19, 20] that have been conducted, found that practitioners had positive attitudes towards and were satisfied with CPGs. This was because of the potential of CPGs to reduce risk and variation in healthcare practice, improve safety, and be useful sources of advice for patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found out that the attitude upper latent variable was affected significantly, positively and at a remarkably high level (β = 0.737; p = 0.008) by positive attitude latent variable while it was affected significantly, negatively and at a remarkably high level (β = −0.761; p = 0.015) by negative In this study, the level of agreement (average: 3.61; SD: 0.66) on the expressions under positive attitude dimension was found to be high. Likewise, the level of agreement on these expressions was also found to be high in the international studies (Amer et al, 2018;Basedow et al, 2015;Birrenbach et al, 2016;Bochud et al, 2002;Dye et al, 2000;Farquhar et al, 2002;Ferrier et al, 1996;Formoso et al, 2001;Graham et al, 2000;Gupta et al, 1997;Halm et al, 1999;Heidrich et al, 2005;Helwig et al, 1998;Hendaus et al, 2014;Heselmans et al, 2009Heselmans et al, , 2010Inouye et al, 1998;James et al, 1997;Kim et al, 2010;Kunz, 2005;Larisch et al, 2009;Mansfield, 1995;Mounesan et al, 2013;Sinuff et al, 2007;Siriwardena, 1995;Taba et al, 2012;Tunis et al, 1994;Wahabi et al, 2011;Wolff et al, 1998).…”
Section: Discussionmentioning
confidence: 87%
“…The physicians working in a public education and research hospital in Ankara comprised the research population. The questionnaire, which was used as a data collection tool, consisted of three main sections: the first section included the questions about sociodemographic characteristics of the participants, and the second section included 18 expressions to investigate positive and negative attitudes against the CPGs which were obtained from a detailed literature review (Amer et al, 2018; Basedow et al, 2015; Birrenbach et al, 2016; Bochud et al, 2002; Dye et al, 2000; Farquhar et al, 2002; Ferrier et al, 1996; Flores et al, 2000; Formoso et al, 2001; Graham et al, 2000; Gupta et al, 1997; Haagen et al, 2005; Halm et al, 1999; Hayward et al, 1997; Heidrich et al, 2005; Helwig et al, 1998; Hendaus et al, 2014; Heselmans et al, 2009, 2010; Inouye et al, 1998; James et al, 1997; Kalies et al, 2017; Kim et al, 2010; Kunz, 2005; Larisch et al, 2009; Mansfield, 1995; Mounesan et al, 2013; Pogorzelska & Larson, 2008; Reiner et al, 2010; Sinuff et al, 2007; Siriwardena, 1995; Taba et al, 2012; Tunis et al, 1994; Wahabi et al, 2011; Wolff et al, 1998). The attitudes measured with 18 expressions against CPGs that were assessed by using a 5-point Likert scale formed in the type of (1) I certainly do not agree and (5) I certainly agree.…”
Section: Methodsmentioning
confidence: 99%